Independence of PEMRA and Regulatory Framework of Electronic Media in Pakistan - Fatiana, Yasir Aleem; Abdul Wahab, Harlida; Halim, Rohizan (Research Gate, 2018)
This article analytically examine the history and present situation of regulatory process of electronic media in Pakistan. This paper also explore as to what extent PEMRA as a regulatory authority is operating independently under the existing law. This article concludes that PEMRA should be granted more institutional independence in order to effectively regulate electronic media in Pakistan